2009
DOI: 10.1243/09544054jem1392
|View full text |Cite
|
Sign up to set email alerts
|

Influences of disturbance frequency on the droplet generation for microdroplet deposition manufacture

Abstract: The influences of the disturbance frequency on the metal droplet generation are investigated for microdroplet deposition manufacture. The polynomial distribution model is assumed for the jet velocity profile. The optimal disturbance frequency is predicted according to the linear stability analysis. The jet velocity converges and the uniform droplets are generated at the optimal disturbance frequency in the simulation. Experiments have been conducted with the orifice diameter of 150 mm. The formation and diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As a result, it is theoretically and experimentally confirmed that there are inherent transverse oscillations in the jet by changing the radial velocity component. Similar studies on the effect of oscillation frequency on the stability of the droplet shape [26] and its monodispersity [27] are additionally presented in the works [28,29].…”
Section: Introductionmentioning
confidence: 63%
“…As a result, it is theoretically and experimentally confirmed that there are inherent transverse oscillations in the jet by changing the radial velocity component. Similar studies on the effect of oscillation frequency on the stability of the droplet shape [26] and its monodispersity [27] are additionally presented in the works [28,29].…”
Section: Introductionmentioning
confidence: 63%
“…The part was fabricated with the UDS method showed a 30 percent improvement the Mechanical property in ultimate tensile strength compared to raw stock. Northwestern Polytechnical University [6,7] also has done some researches with UDS. But this technique produces a continuous stream of droplets at very high frequencies (4~20 KHz), which makes this method difficult to control.…”
Section: Introductionmentioning
confidence: 99%